Biocathodes reducing oxygen at high potential select biofilms dominated by Ectothiorhodospiraceae populations harboring a specific association of genes. (August 2016) - Desmond-Le Quéméner, Elie; Rimboud, Mickaël; Bridier, Arnaud; Madigou, Céline; Erable, Benjamin; Bergel, Alain; Bouchez, Théodore
Graphical abstract: Highlights: 10 biocathodes were formed at +0.1 V and −0.4 V vs. SCE. 4 biocathodes active at +0.1 V vs. SCE have been obtained. Most efficient cathodic biofilms are dominated by Ectothiorodospiraceae. The most efficient biofilm was characterized by shotgun metagenomics. Candidate genes implicated in electron transfer and autotrophic growth are outlined. Abstract: Biocathodes polarized at high potential are promising for enhancing Microbial Fuel Cell performances but the microbes and genes involved remain poorly documented. Here, two sets of five oxygen-reducing biocathodes were formed at two potentials (−0.4 V and +0.1 V vs. saturated calomel electrode) and analyzed combining electrochemical and metagenomic approaches. Slower start-up but higher current densities were observed at high potential and a distinctive peak increasing over time was recorded on cyclic voltamogramms, suggesting the growth of oxygen reducing microbes. 16S pyrotag sequencing showed the enrichment of two operational taxonomic units (OTUs) affiliated to Ectothiorodospiraceae on high potential electrodes with the best performances. Shotgun metagenome sequencing and a newly developed method for the identification of Taxon Specific Gene Annotations (TSGA) revealed Ectothiorhodospiraceae specific genes possibly involved in electron transfer and in autotrophic growth. These results give interesting insights into the genetic features underlying the selection of efficient oxygen reducing microbes on biocathodes.